Effect of alcoholic phenol and nanocapsules extract from grape seed (Vitis vinifera) on egg hatching and adult death of southern cowpea beetles - A.S. Mall, Rusul; Sahar A. Kathier (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Pulses are the second most significant economic crop that have been attacked by many storage pests. One of these pests is the cowpea beetle (Callosobruchus maculatus).  This study aims to study the effect of phenol  grape seed (Vitis vinifera) extract (1000,1500,2000,2500and 3500 mg/L) on eggs and adults. The results showed that the alcoholic extract of the grape seed (Vitis vinifera) recorded for the egg hatching was (80, 56.67, 53.33, 40.00 and 10.00%) respectively, Results in the use of nanocapsules at concentrations of 100 and 500 mg/L showed the egg hatching ratio was (53.33, 16.67%) respectively, while the results of alcoholic extracts of grape seed (Vitis vinifera)  recorded for adult mortality was(20.00, 70.00, 73.33, 76.67and96.67%) respectively after 72 hours of treatment , Results in the use of nanocapsules at concentrations of 100 and 500 mg/L showed the adult mortality rate was (26.67, 93.33%) respectively after 72 hours of treatment , The adult mortality rate increases by increasing the concentrations.